Soil Carbon Pool Under Salix alba Plantations and Adjacent Bare Soils In Temperate Regions of Kashmir - Murtaza, Shah; Masoodi, T. H.; Naseem Zafar, S.; Gatoo, Aasif A.; Wani, Akhlaq A.; Wani, J. A. (Indian Forester, 2018)
The present investigation was carried out under the willow plantations established by Plantation Division of State Forest Department in Anantnag, Bandipora, Baramulla and Ganderbal Districts of Kashmir valley. Two plantation blocks of willow were selected in each District The existing Soil organic carbon, bulk density and soil carbon sequestration under Salix trees at all the selected locations were determined. The mean values for bulk density obtained from the different sites exhibit a significant variation while was found non-significant during the period of investigation. Soils under the plantations at Bandipora exhibited lowest bulk density of 1.299 g cm3, while the soils at Anantnag had the maximum values of 1.360 g cm*. The maximum soil carbon density of 68.07 t ha’1 was recorded at Bandipora, followed by 67.931 ha’1 at Baramulla, 66.861 ha’1 at Ganderbal and 66.431 ha’1 at Anantnag. The results indicate that there was a significant (p<0.05) periodic (CAI) stratification in soil carbon density values recorded during the period of investigation. Maximum (4.6611 ha1] annual addition in SOC was recorded under the canopy of willow trees at Bandipora, the least yearly accretion (4.416 t ha1) was exhibited by soils developing under the canopy of this species at Anantnag. The data further envisages that SOC recorded in soil samples collected from adjacent fallow lands were far less (34-50%) as compared to those obtained under the canopy of willow plantations at all the locations.